ETIKA WAYANG DALAM NOVEL-NOVEL INDONESIA - Kustri Sumiyardana (Madah: Jurnal Bahasa dan Sastra, 2015)
Literary has closed relationship with culture. Authors often include cultural elements to influence it in their literary works. It is also done by Javanese authors who write Indonesian novels. Some authors include the story of wayang in their novels. By analyzing with textual method, this research described wayang ethics that existed in four Indonesian novels. Based on the analysis, it can be concluded that the authors often include the elements from wayang story due to the fact that wayang is main identity of Javanese people. The wayang elements in Indonesian novels are the plot of the story that identical with wayang acts and the figures are created similarly with the figures in wayang story. The similarities showed there some figures in wayang story who became the idols in society.